PENINGKATKAN PARTISIPASI AKTIF PARA PELAYAN DI GKJ WIROBRAJAN MELALUI IBADAH PADANG PASKA PANDEMI COVID-19 - Minarni, Nani; Purwadi, Joko; Haryono, Nugroho Agus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2023)
Abstract This paper is the result of the leadership training that was conducted by the DWCU Faculty of Information Technology Service Team in the first of the three stages of mentoring that was agreed by the GKJ Wirobrajan assembly. The leadership training was intended for church activists, consisting of assemblies, commissions and regional administrators, with the aim of strengthening motivation as servants at GKJ Wirobrajan after the COVID-19 pandemic. The next goal is to introduce a steward leader model in the church that emphasizes a participatory approach in the ministry of the church, so that it does not rely on the pastor as the figure of the church. The final result from the leadership training is that the servants of the church can reinterpret their understanding of the meaning of service, a participatory approach in ministry and have a commitment to serve that is heard and supported by the other church activists. To achieve this goal, the method used in the leadership training is interactive -reflective, with a training flow done in the form of a combination of models between worship, lectures, group dynamics, and self-reflection. The final result that can be obtained after the training of the first stage of the board has three important things as the basis for the next stage, namely interpreting the meaning of authenticity service, a new awareness of being a participatory servant, and personal reflection that touches the spiritual aspect of a servant. Keywords: GKJ Wirobrajan, Service, Steward Leaders, Interactives-Reflective, Participatory Approach